Planned obsolescence Understanding the reality of durable goods obsolescence and consumers' disposal behaviour - Nejedlá, Jana; Pešek, Ondřej; Štědroň, Bohumír, 1948-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2011)
Planned obsolescence is the term used to describe incentives of companies to make durable goods faster obsolete. The aim of the study is to make a big picture and real situation about planned obsolescence practising and consumer disposal behaviour. First part addresses the theoretical background and provides comprehensive overview through different aspects of the good's durability issue and planned obsolescence characteristics and influences. Second part in further reference to the information provided in theoretical part examines the situation of specific durable products - laptops. From survey's results on consumer attitudes towards durability of laptops and real case study on Apple Inc. and its reliance to planned obsolescence, recommendations to the more sustainable consumption of consumer electronics are presented.
Vedoucí práce: Ondřej Pešek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2011
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2011
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses